High efficiency water splitting photoanodes composed of nano-structured anatase-rutile TiO2 heterojunctions by pulsed-pressure MOCVD - Gardecka,AJ; Bishop,C; Lee,D; Corby,S; Parkin,IP; Kafizas,A; Krumdieck,S (Applied Catalysis B: Environmental, 2017)
In this article, thin solid films are processed via pulsed-pressure metal organic chemical vapour deposition (PP-MOCVD) on FTO substrates over a range of processing times to produce a range of thicknesses and microstructures. The films are highly nanostructured anatase-rutile TiO2 composite films with unique single crystal dendrites. After annealing, carbon was removed, and materials showed improved water splitting activity; with IPCEs above 80% in the UV, photocurrents of ∼1.2 mA cm−2 at 1.23 VRHE at 1 sun irradiance and an extension of photoactivity into the visible range. The annealed material exhibits minimal recombination losses and IPCEs amongst the highest reported in the literature; attributed to the formation of a high surface area nanostructured material and synergetic interactions between the anatase and rutile phases.